THE INFLUENCE OF THE SURVEY, QUESTION, READ, RECITE REVIEW, AND REFLECT (SQ4R) METHOD TOWARD THE STUDENTS’ READING COMPREHENSION (A STUDY OF META-ANALYSIS) - Muhamad Ardianto Rumasera; St. Azisah (International Conference on Social and Islamic Studies, 2021)
This research aims to analyze the average level of influence of the SQ4Rmethod on reading comprehension as a whole, based on education levels, and based onthe regions. The research method used is a quantitative method with a meta-analysisdesign, namely by analyzing the results of research that have been published nationallyrelated to the influence of the SQ4R method on reading comprehension. The documentsources analyzed in this research were twenty articles and thesis obtained through GoogleScholar search published in the 2015-2021 range covering the educational levels ofElementary School, Junior High School, Senior High School, and University, whichdiscussed using the SQ4R method on reading comprehension. The instrument usedcoding sheet that summarizes the data and information of the articles and thesis. Based onthe average level of influence of the SQ4R method on reading comprehension as a wholeis 0.893 high category. The average level of influence of the SQ4R method on readingcomprehension based on education levels, in Elementary School is 0.741 mediumcategory, Junior High School is 0.961 high category, Senior High School is 0.988 highcategory, and University is 0.594 medium category and also the average level ofinfluence of the SQ4R method on reading comprehension based on regions, Java Region0.843 high category, Bali 0.922 high category, Lampung 0.339 small category,Kalimantan 0.406 small category, Sumatera 0.943 high category, Aceh 0.989 highcategory and Riau 0.571 medium category. The conclusion that the average level ofinfluence SQ4R method reading comprehension as whole is 0.839 in high category, itmeans that SQ4R is very suitable method on teaching reading comprehension. Based oneducational levels, the SQ4R method on reading comprehension is suitable to conduct forall levels of education, and Based on regions, in high and medium category is Java, Bali,Sumatera, Aceh and Riau, it means that the SQ4R method on reading comprehensionmany gave contributions in five of regions.